An increase in sludge loading rate induces gel fouling in membrane bioreactors treating real sewage. (December 2022) - Miwa, Toru; Takimoto, Yuya; Mizuta, Yuki; Hatamoto, Masashi; Watari, Takahiro; Yamaguchi, Takashi
Abstract: The main objective of this study was to investigate the cause of gel fouling in membrane bioreactors (MBRs) treating real sewage in terms of soluble microbial products (SMPs) and microbial aspects. Two anoxic/oxic-MBRs were operated as the control reactor (S1) and the sludge loading rate increased reactor (S2). The reactors were operated under low-temperature around 11 °C conditions. Membrane permeability substantially decreased in S2, and gel layer biofilm was formed on membrane surface. In contrast, the permeability of S1 gradually decreased and cake layer formed. When gel fouling occurred, the protein and polysaccharide of SMP in S2 were 47 and 23 mg L −1, which were significantly lower than those recorded in S1 accounted for 118 and 68 mg L −1, respectively. Furthermore, the total organic carbon concentration of SMPs was 24 mg L −1, which was lower than the influent in S2, accounted for 62 mg L −1 . Finally, Campylobacteraceae which exists in sewage and uncultured OD1, dominated the gel layer biofilm in S2, unlike the cake layer biofilm in S1. These results indicated that the gel layer biofilm might be composed of influent substances, demonstrating the importance of influent decomposition in MBR for gel fouling mitigation. Graphical abstract: Image 1 Highlights: Low temperature and sludge loading rate change induced gel fouling. The lowest SMP concentration exhibited at the highest sludge loading rate. Sludge filterability was not associated with gel fouling occurrence. Sewage derived bacteria was dominant in gel layer on membrane surface.